2018
DOI: 10.1016/j.redox.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

AKT-independent activation of p38 MAP kinase promotes vascular calcification

Abstract: Vascular calcification is prevalent in patients with atherosclerosis, and oxidative stress promotes pathogenesis of atherosclerosis. We have previously reported that activation of AKT by oxidative stress induces vascular calcification. Using sodium dichloroacetate (DCA), a previously reported small molecule inhibitor of AKT, the present studies uncovered an AKT-independent mechanism in regulating vascular calcification.We found that DCA dose-dependently induced calcification of vascular smooth muscle cells (VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
(81 reference statements)
1
28
0
Order By: Relevance
“…Here, we showed that incubation of PC with 1,25(OH) 2 D 3 activates p38. This is consistent with the reported role of p38 activation in VSMC calcification . However, VEGF, PDGF, or their combination did not activate p38 (Figure A,D).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Here, we showed that incubation of PC with 1,25(OH) 2 D 3 activates p38. This is consistent with the reported role of p38 activation in VSMC calcification . However, VEGF, PDGF, or their combination did not activate p38 (Figure A,D).…”
Section: Resultssupporting
confidence: 92%
“…The MAPK family of proteins including ERKs and p38, and AKT signaling pathways are involved in regulation of diverse range of cellular processes including 1,25(OH) 2 D 3 ‐mediated VSMC osteoblastic differentiation and calcification . We showed incubation of retinal PC with 1,25(OH) 2 D 3 resulted in p38 and ERK activation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Pdk knockdown exacerbated the developmental delay of tko 25t (Figure 6(b), ii), but only under conditions of pyruvate overload. Although DCA is a potent inhibitor of Pdk [53], it may also have other targets [54][55][56] and is accumulated in cells via the plasmamembrane monocarboxylate transporters, MCTs [57]. Moreover, in cancer cells, it has been reported to inhibit the pentose phosphate pathway [58] and thereby decrease the level of NADPH, which is already depleted in tko 25t , especially when grown on high-sugar medium [7].…”
Section: Tissue-specificity Of the Bang-sensitive Phenotypementioning
confidence: 99%